Instant Web forms and surveys for academic libraries - Junion-Metz, Gail, 1947-; Metz, Derrek L. (New York : Neal-Schuman, 2001)
Contains twenty-four customizable academic library forms and surveys in HTML format. Includes matching Perl scripts and tutorial
Book is accompanied by one CD-ROM bearing the same call number and available at Koleksi Media, Perpustakaan PPUKM
System requirements: PC; Windows
Keywords: Academic libraries -- Forms; Library surveys; Library information networks